Conceptual and procedural errors of pre-service elementary teachers in solving educational research statistics problems - Siti Maryam Rohimah; Sarah Anida Putri; Yullys Helsa (Jurnal Elemen, 2026)
Pre-service elementary teachers often make errors in educational research and problem-solving, highlighting the need to examine the nature and causes of these errors. This study employed a qualitative descriptive case study design to identify the types of errors made by Elementary School Teacher Education (ESTE) students in solving educational research statistics problems and to examine the factors contributing to these errors. The participants were 58 ESTE students enrolled in a statistics course at a private university in Indonesia. Data were collected through problem-solving tests, interviews, and classroom observations. The test instrument was used to assess students’ understanding of statistical concepts, while interviews and observations explored cognitive and contextual factors influencing error occurrence. The findings indicate that conceptual errors occurred in 17% of cases and procedural errors in 22%. Conceptual errors were primarily due to difficulties interpreting statistical software outputs, whereas procedural errors were associated with inaccuracies in applying formulas and performing calculations. These findings contribute to a clearer theoretical understanding of conceptual and procedural errors in statistics learning and highlight the need for instructional approaches that balance conceptual and procedural aspects in educational research statistics.